Lipid metabolism disturbance and immune dysfunction in HBV-related acute-on-chronic liver failure: a retrospective cohort study - Neng Wang; Yu Zheng; Shuai Tao; Liang Chen (BMC Gastroenterology)
Abstract Objective This study aimed to elucidate the correlations among dyslipidemia, immune function, and clinical outcomes in patients with acute-on-chronic liver failure (ACLF), with particular emphasis on the clinical significance of lipid metabolism and cellular immune parameters in hepatitis B virus-associated ACLF (HBV-ACLF). Methods A retrospective analysis was conducted on 803 patients with HBV-ACLF admitted to the Shanghai Public Health Clinical Center from January 2014 to January 2024. Patients were stratified into deceased (n = 414) and survival (n = 389) groups based on clinical outcomes. Clinical baseline data, lipid metabolic indices, and cellular immune parameters were collected. The Spearman correlation coefficient was utilized to assess the correlation between lipid metabolic indices and cellular immune parameters, and a multivariate Cox proportional hazards model was applied to analyze risk factors for mortality. Results Compared to the survival group, lipid metabolism indices in the deceased group were significantly reduced (P < 0.05). Lipid metabolism indices, including high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), apolipoprotein A1 (APOA1), apolipoprotein B (APOB), total cholesterol (TC), and triglycerides (TG), demonstrated significant negative correlations with the severity of liver failure (P < 0.05). Correlation analysis with lymphocyte subset counts revealed positive correlations between low-density lipoprotein, TG, TC, APOB, and CD3 + T cells, CD4 + T cells, CD8 + T cells, and CD45 + T cells (P < 0.05). APOA1 and HDL-C were positively correlated with B cells and NK cells (P < 0.05). TG and APOB showed significant negative correlations with the CD4/CD8 ratio (P < 0.05). Multivariate Cox analysis identified age, creatinine, total bilirubin, international normalized ratio (INR), hepatic encephalopathy, and hepatorenal syndrome as independent risk factors affecting the short-term prognosis of HBV-ACLF, while sodium, APOA1, and APOB were identified as independent protective factors for ACLF (HR = 0.984, 95% CI: 0.974–0.995, P < 0.001, HR = 0.267,95% CI: 0.120–0.596, P = 0.001, HR = 0.486, 95% CI: 0.282–0.838, P = 0.010). Conclusion Patients with HBV-ACLF exhibit decreased levels of TC, TG, LDL-C, HDL-C, APOA1, and APOB. These alterations in serum lipid profiles are associated with immune dysfunction and disease progression in HBV-ACLF. Notably, APOA1 and APOB serve as protective factors against 90-day mortality in hospitalized ACLF patients. Further investigation is warranted to elucidate the relationship between lipid metabolism disturbances and peripheral immunity in ACLF.